Evaluation of remineralizing potential of commercially available child formula dentifrices: An in vitro study - Apurva Jagdish Gujarathi; Santosh M Sholapurmath; Praveenkumar S Mandroli; Deepa B Benni (Wolters Kluwer Medknow Publications, 2015)
Aim: The aim of this in vitro study is to evaluate the remineralizing potential of commercially available low fluoride child formula dentifrice on primary teeth. Materials and Methods: Total 30 primary teeth were placed in demineralizing solution for 96 hours to produce artificial carious lesions of approximately 100 μm depth, and then cut longitudinally into 30 sections of 100-150 μm thickness and randomly assigned to three groups. Sections were treated with dentifrices containing Colgate ® (anti tooth decay) 500 ppm NaF, Cheerio gel ® 458 ppm MFP and Vicco ® non-fluoridated dentifrice. Lesions were evaluated using polarized light microscopy. Results: Colgate ® (anti tooth decay) 500 ppm NaF sections exhibited a statistically significant decrease in lesion depth (P < 0.05, paired t-test), whereas those in Cheerio gel ® 458 ppm MFP showed a decrease in lesion depth but was not statistically significant. Vicco ® non-fluoridated dentifrice showed increase in lesion depth. Statistics: A paired t-test is used to evaluate pre- and post-treatment lesion depth measurements, and Newman-Keuls multiple post hoc procedures was carried out to compare pair-wise difference of pre- and post-treatment lesion depth. Conclusion: The Colgate ® (anti tooth decay) 500 ppm NaF dentifrice and Cheerio gel ® 458 ppm MFP demonstrated remineralization of carious lesions by virtue of decrease in lesion depth, whereas Vicco ® non-fluoridated dentifrice showed increase in lesion depth.